Modelling the Condensation Phenomena within the Radial Turbine of a Fuel Cell Turbocharger - Tim Wittmann; Sebastian Lück; Christoph Bode; Jens Friedrichs (International Journal of Turbomachinery, Propulsion and Power, 2021)
Radial turbines used in automotive fuel cell turbochargers operate with humid air. The gas expansion in the turbine causes droplets to form, which then grow through condensation. The associated release of latent heat and decrease in the gaseous mass flow strongly influence the thermodynamics of the turbine. This study aims to investigate these phenomena. For this purpose, the classical nucleation theory and Young’s growth law are integrated into a Euler–Lagrange approach. The main advantages of this approach are the calculation of individual droplet trajectories and a full resolution of the droplet spectrum. The results indicate an onset of nucleation at the blade tip and in the tip gap, followed by nucleation over the entire blade span, depending on the humidity at the turbine inlet. With a saturated turbine inflow, condensation causes the outlet temperature to rise to almost the same level as at the inlet. In addition, condensation losses reduce the efficiency and the latent heat released by condensation leads to significant thermal throttling.